Grade 11 Students’ Multiple Intelligences: Inputs Towards Developing and Evaluating Technologically-Mediated Learning Materials on Discourse Development Patterns - Discutido, Roy A. (Future Science / FSH-PH Publications, 2022)
Learners around the world possess varying degrees of intelligence. With that, teachers should be aware of the multiple intelligence of the learners to consider them when preparing teaching materials or classroom activities. This is to aid the deteriorating performance of the learners specifically in language learning. As seen in the results of international assessments or even in national achievement tests, learners showed that they were not able to master the required competencies and one of the reasons is the ability to comprehend. This study aimed to determine the extent of use of the multiple intelligences of the Grade 11 students of Cainta Senior High School in the Division of Rizal which served as inputs in developing and evaluating technologically-mediated learning materials on discourse development patterns during the school year 2020-2021. With two groups of respondents, the students and the teachers, the developed material based on the multiple intelligence of the learners was evaluated in terms of authenticity, automaticity, clarity, comprehensibility, meaningfulness, and technicality. Using t-test, the gathered data was treated. The results revealed that there is no significant difference between the evaluation of students and teacher respondents whom both said that the technologically-mediated language learning material is very highly acceptable for teaching and learning the different discourse development patterns using the students’ multiple intelligences.